Development of an Indirect ELISA to Detect African Swine Fever Virus pp62 Protein-Specific Antibodies - Zhong, Kexin; Zhu, Mengmeng; Yuan, Qichao; Deng, Zhibang; Feng, Simeng; Liu, Daoxin; Yuan, Xiaomin (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly detrimental viral disease caused by African swine fever virus (ASFV). The occurrence and prevalence of this disease have led to serious threat to the global swine industry and national economies. At present, the detection volume of African swine fever is huge, more sensitive and accurate detection techniques are needed for the market. pp62 protein, as a protein in the late stage of infection, has strong antigenicity and a high corresponding antibody titer in infected pigs. In this study, the CP530R gene was cloned into expression vector pET-28a to construct prokaryotic expression plasmid, which was induced by IPTG to express soluble pp62 protein. Western blot analysis showed that it had great reactivity. Using the purified recombinant protein as antigen, an indirect ELISA method for detecting ASFV antibody was established. The method was specific only to ASFV positive serum, 1:1600 diluted positive serum could still be detected, and the coefficients of variation (CV) of intra assay and inter assay were both less than 10%. It turns out that the assay has excellent specificity, sensitivity and repeatability. This provides an accurate, rapid and economical method for the detection of ASFV antibody in clinical pig serum samples.